View of the hotel of the Hungarian noble guard on the Glacis (Trautson Palace) - Geissler, Maria (publisher):::Creator:::::::::::: (Austria; Maria Geissler; Vienna, 2020)
Miniature color engraving of the Trautson Palace in Vienna